Therapeutic Potential of a Prolyl Hydroxylase Inhibitor FG-4592 for Parkinson’s Diseases in Vitro and in Vivo: Regulation of Redox Biology and Mitochondrial Function - Li, Xuan; Cui, Xin-Xin; Chen, Ya-Jing; Wu, Ting-Ting; Xu, Huaxi; Yin, Huiyong; Wu, Yun-Cheng (Frontiers in Aging Neuroscience, 2018)
As the main transcription factor that regulates the cellular responses to hypoxia, Hypoxia-inducible factor-1α (HIF-1α) plays an important role in the pathogenesis of Parkinson's disease (PD). HIF-1α is normally degraded through ubiquitination after hydroxylation by prolyl hydroxylases (PHD). Emerging evidence has suggested that HIF PHD inhibitors (HIF-PHI) may have neuroprotective effects on PD through increasing HIF-1α expression. However, the therapeutic potential of HIF-PHI for PD remain poorly explored due to the lack of proper clinical compounds and understanding of the underlying molecular mechanisms. In this study, we examined the therapeutic benefit in PD models using a new HIF-PHI, FG-4592, which is currently in phase 3 clinical trials to treat anemia in patients with chronic kidney diseases (CKD). FG-4592 attenuated MPP+ -induced apoptosis and loss of tyrosine hydroxylase (TH) in SH-SY5Y cells. Pretreatment with FG-4592 mitigated MPP+-induced loss of mitochondrial membrane potential (MMP), mitochondrial oxygen consumption rate (OCR), production of reactive oxygen species (ROS) and ATP. Furthermore, FG-4592 counterbalanced the oxidative stress through up-regulating nuclear factor erythroid 2 p45-related factor 2 (Nrf-2), heme oxygenase-1 (HO-1) and superoxide dismutase 2 (SOD2). FG-4592 treatment also induced the expression of Peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) through increasing the phosphorylation of AMP-activated protein kinase (AMPK). In MPTP-treated mice, FG-4592 protected against MPTP-induced loss of TH-positive neurons of substantia nigra and attenuated behavioral impairments. Collectively, our study demonstrates that FG-4592 is a promising therapeutic strategy for PD through improving the mitochondrial function under oxidative stress.